CASE STUDY: ALTERNATIVE DISPUTE RESOLUTION FOR THE DIVISION OF AN INHERITANCE BETWEEN STEPCHILDREN AND CHILDREN BORN OUT OF WEDLOCK - Noer Zaini Khalis; Muhammad Yadi Harahap; Abdul Mukhsin (Jurnal Ikhtibar Nusantara, 2026)
Disputes in the distribution of inheritance often occur in families, especially those involved are stepchildren and adulterous children who differ in the inheritance distribution system. In general, stepchildren are not related by bloodline through their stepfather or stepmother. While the child resulting from adultery only has a bloodline relationship with their mother. This difference in status often causes disputes in the distribution of inheritance. Therefore, this study aims to determine what the legal status of stepchildren and adulterous children in the distribution of inheritance according to Islamic law and to analyze alternative solutions for resolving disputes that can be used to resolve them. Therefore, the method used in this study is a normative method with a legislative approach and literature study through Islamic legal sources, the Compilation of Islamic Law (KHI), and related existing literature. The results of this study indicate that stepchildren and adulterous children basically do not receive inheritance rights from parties who are not related to them. However, there are several ways to resolve this dispute through family deliberation, grants, wills, mandatory wills, and mediation in order to realize justice and maintain family harmony. Therefore, resolving inheritance disputes requires consideration of applicable legal mechanisms, both Islamic and common law, that prioritize the mutual benefit of all parties